Fault ride-through capability enhancement of doubly-fed induction wind generators - Mohseni, Mansour; Islam, Syed; Masoum, Mohammad Sherkat (The Institution of Engineering & Technology (IET), 2011)
Recent fault ride-through (FRT) requirements have proven problematic for variable-speed wind generation systems. A particular problem regarding to doubly-fed induction generators (DFIGs) is that standard proportional integral (PI) current controllers, designed with very limited control bandwidth, cannot eliminate rotor current oscillations that occur during a grid fault. As a consequence, the current in the rotor-side converter can exceed the safety limits of semiconductor switches, which potentially leads to converter failure. This study introduces a hybrid current controller to enhance the FRT capability of DFIGs through keeping the rotor current below the safety limits. The proposed current controller includes two switching strategies: the standard PI current controller for normal operating conditions and a vector-based hysteresis current controller (with very fast transient response) for overcurrent protection during grid faults. Simulation studies are carried out to demonstrate the effectiveness of the proposed hybrid current controller under various symmetrical and asymmetrical voltage sag conditions.